THE CONCEPT OF FOOD SAFETY AND ITS SCIENTIFIC CONCEPT - Bobir Tursunov; Sherali Namozov (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes methodological approaches that are conditioned by the importance of food security. The stages of the concept of food security were defined. The theory of food security has been improved in terms of organizational, legal and economic criteria.